Analisis Pengendalian Kualitas Pada Tempe Menggunakan Metode Seven Tools - Ruth Veronika Zendrato; Ryantama Ryantama; Muhammad Agung Nugroho; Destiana Putri; Dwiyanto Kuncoro; Sepriandi Parningotan (IMTechno: Journal of Industrial Management and Technology, 2022)
Basically, product quality is one of the important factors that becomes one of the benchmarks for the success of a product and the future of a company. Even though the production process is carried out well, the resulting product is often not as desired, or in other words it produces a damaged/defective product. The presence of defective products will reduce product quality and this causes losses to the business. To meet consumer satisfaction, business actors must be able to maintain product quality in accordance with consumer needs, in quality control which is very much needed to control the production process so that it conforms to predetermined standards. Small and Medium Industrial Factory (IKM) Bapak Warianto is one of the tempe production factories where in the tempe production process he found several tempe defects ranging from color, shape, to the packaging of the tempe that could not be sold. This research, which was conducted at tempe factory Bapak Warianto, aims to identify quality problems in tempe products, analyze the causal factors in tempe products and provide solutions to improve the tempe production process. The Seven Tools Method is the method that will be used in this research, where this method consists of several statistical tools that are used to determine product quality. From 10 sampling times, there were 4 types of defects in tempeh, of which the four types of defects were eaten as the most dominant/frequent defects. This is because the storage area for tempeh when fermented is not clean and not covered enough so that small animals can still enter. Lack of air circulation and human factors where workers are not careful are also some of the causes of damage to tempe.